SAT0272 Serum Ctx-I Predicts Systemic Bone Loss at the Hip Over 1 Year in Patients with Early Psoriatic Arthritis. (23rd January 2014) - Szentpetery, A.; Kilbane, M.; O'Keane, M. P.; Haroon, M.; Gallagher, P.; van der Kamp, S.; McKenna, M. J.; FitzGerald, O.
Abstract : Background: There is a growing interest in bone and cartilage biomarkers that could be used predicting and assessing changes in structural damage in inflammatory arthritis. Disease-related bone loss assessed by dual-energy X-ray absorptiometry (DXA) is a well known feature in RA and PsA, however data on bone loss during the first year of treatment in early disease are limited. Objectives: (1) To study changes in serum levels of bone biomarkers and bone mineral density (BMD) measurements in early PsA and RA prior to and 12 months after introducing an anti-rheumatic drug; (2) To explore associations between disease-related variables, serum bone biomarkers and BMD measurements; (3) To investigate if serum bone biomarkers prior to treatment predict systemic bone loss over 1 year in patients with PsA and RA. Methods: Recent-onset (<12 months), active, treatment naive PsA and RA patients were recruited. We measured serum bone-specific alkaline phosphatase (bone ALP), a marker of bone formation, and C-terminal cross-linking telopeptide (CTX-I), a degradation marker of type-I collagen reflecting systemic bone resorption at baseline, 3 and 12 months by immunoassay. We assessed bone remodelling balance by calculating bone ALP/CTX-1 ratios. BMD measurements were obtained at left total hip and lumbar spine at baseline and 12 month by DXA. Clinical parameters were correlated with bone biomarkers and BMD measurements. Results: 64 patients (32 PsA, 32 RA) were included with median age 43 years. 95% of the patients were commenced on a DMARD therapy at baseline and 11.7 % (12.5% RA; 10.7% PsA) were also started on a TNF inhibitor. At 12 months 94.8% of the patients were on a DMARD and 34.5% on TNF inhibitor (33.3 % RA; 35.7% PsA). Bone ALP levels did not change significantly in either cohort during the study. CTX-I levels decreased after 3 months of treatment in RA (p=0.013) and in the entire group (p=0.043) remaining lower at 12 months (p= 0.042; p= 0.012 respectively) compared to baseline. Bone ALP/ CTX-I ratio was higher (p=0.05) at 1 year compared to baseline in the entire group reflecting improvement in bone remodelling balance. Hip BMD decreased in both diseases, significantly in RA (p=0.021), whilst spine BMD decreased in RA (p=0.056) but increased in PsA (p=0.017). CTX-I levels were correlated inversely with hip BMD in PsA at both baseline and 12 months (r = -0.38, p= 0.04; r = -0.51, p= 0.007) and similarly in the entire group (r = -0.29, p= 0.03; r = -0.3, p= 0.02). Baseline CTX-I levels correlated with the change in hip BMD over 12 month in the whole group (r = 0.31, p= 0.03). Stepwise multiple logistic regression analysis revealed significant associations of baseline CTX-I levels with change in BMD of the hip over 12 months in PsA (OR 2.8, p=0.009) and in the entire cohort (OR 2.5, p=0.014) with the model also including bone ALP, ESR, CRP, DAS28 CRP and HAQ. Conclusions: The improvement in bone remodelling balance seen in early PsA and RA patients is most likely due to decrease in bone resorption after 1 year of appropriate anti-rheumatic therapy. High baseline levels of serum CTX-I may predict systemic bone loss at the hip over 1 year in patients with PsA. Disclosure of Interest: A. Szentpetery: None Declared, M. Kilbane: None Declared, M. O'Keane: None Declared, M. Haroon: None Declared, P. Gallagher: None Declared, S. van der Kamp: None Declared, M. McKenna: None Declared, O. FitzGerald Grant/research support from: Abbott, BMS, Pfizer, MSD, Consultant for: Abbott, UCB, Pfizer, Speakers bureau: Abbott, Pfizer, MSD